ANALISA KEGAGALAN PADAVELG MOBIL MITSUBISHI L300 BERBASIS LOGAM BAJA - Hasrad .; Muhammad Sabri; Syahrul Abda; Ikhwansyah Isranuri; Mahadi . (Jurnal Dinamis, 2016)
Steel wheels have called the critical area is located in the hub, spokes, and flange. Failure to flange area can result in loss of many parties, both in terms of loss of material and non-material terms. The purpose of this research is expected strength steel alloy can be increased without the need to add special alloying elements. Object of the research is the former steel car wheels Mitsubishi 14 inch diameter (355.6 mm) and a width of 5 inches (127 mm). Tests were conducted chemical composition test, hardness test, tensile test, metallographic test. Of testing found that the composition of the alloy material is steel on wheels mark. Violence on the material in the rim flange area that normally is 121 BHN scale. Violence in the plastically deformed flange is 89.3 BHN scale. The maximum tensile stress is 409.610 MPa, elongasinya 5.48%, voltages her mouth 266.207 MPa, Young's modulus 2651 GPa. Micro Photo with 200 x and 500 x magnification obtain porosity occurs in the area of plastic deformation.